Kidney Function Responses to Ethanol Extracts of Chia Seed (Salvia hispanica L.) and Tiger Nut (Cyperus esculentus L.) in Alloxan-Induced Diabetic Rats - Chinyere S. Nwaka; Andrew C. Nwaka (IPS Journal of Basic and Clinical Medicine, 2026)
Diabetic nephropathy is a common and progressive complication of poorly controlled diabetes mellitus, and there is growing interest in plant-derived agents that can slow or reverse this damage. This study evaluated the effect of ethanol extracts of chia seed (Salvia hispanica), tiger nut (Cyperus esculentus), and their combination on kidney function parameters in alloxan-induced diabetic rats. Sixty-three male Wistar rats were assigned to nine groups (n = 7): normal control (A), diabetic untreated (B), diabetic rats given 100 mg/kg metformin (C), diabetic rats given 150 or 300 mg/kg chia seed extract (D, E), 150 or 300 mg/kg tiger nut extract (F, G), and 150 or 300 mg/kg of the chia–tiger nut combination (H, I). Diabetes was induced with a single intraperitoneal dose of 160 mg/kg alloxan monohydrate, and treatments were administered by oral gavage for 21 days. Serum urea, creatinine, sodium, potassium, chloride, and bicarbonate were determined at the end of treatment. Diabetic untreated rats (Group B) showed the most deranged kidney profile, with urea rising to about 12 mmol/l and creatinine to about 80 µmol/l, compared with 6.1 mmol/l and 48 µmol/l in the normal control, alongside elevated sodium, chloride and bicarbonate and reduced potassium. Rats given 300 mg/kg doses of chia seed, tiger nut, and their combination (Groups E, G, and I) maintained kidney parameters close to normal control values, while the 150 mg/kg groups (D, F, H) showed intermediate, partially deranged values. These findings suggest that ethanol extracts of chia seed and tiger nut, particularly at 300 mg/kg and in combination, possess nephroprotective potential in alloxan-induced diabetes, likely mediated by their antioxidant phytochemical content.